Determinants of Tea Trade Potential Between China and Selected ASEAN Countries - Yang, Wei (Wei Yang, 2025)
This study examines the trade potential and factors influencing China’s tea exports to eight ASEAN countries (Cambodia, Indonesia, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam) using data from 1993 to 2022. The RCA model, an extended gravity model, and the PMG panel data analysis are used to explore trade dynamics, influencing factors, and developmental trends. Research highlights China’s and Vietnam’s strong comparative advantages in the tea trade, with China–Thailand trade showing increasing potential. In contrast, Malaysia, Singapore, the Philippines, and Cambodia exhibit weaker competitiveness, while Indonesia’s competitiveness has declined. Key factors positively impacting trade include the GDPs, tea import volumes, and trade dependence of ASEAN countries, while geographical distance and the COVID-19 pandemic negatively affect trade. The trade potential analysis shows that the system has matured, with most ASEAN countries demonstrating indices close to or above 1, particularly Cambodia and Malaysia. Indonesia and Vietnam, however, show unrealized potential. Post-pandemic economic recovery, supported by cooperation and RCEP implementation, has strengthened trade potential. This study provides valuable insights into China’s tea trade competitiveness, offering practical recommendations for optimizing regional trade policies and fostering integration.